14=2u+6(u-3)

Simple and best practice solution for 14=2u+6(u-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14=2u+6(u-3) equation:


Simplifying
14 = 2u + 6(u + -3)

Reorder the terms:
14 = 2u + 6(-3 + u)
14 = 2u + (-3 * 6 + u * 6)
14 = 2u + (-18 + 6u)

Reorder the terms:
14 = -18 + 2u + 6u

Combine like terms: 2u + 6u = 8u
14 = -18 + 8u

Solving
14 = -18 + 8u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-8u' to each side of the equation.
14 + -8u = -18 + 8u + -8u

Combine like terms: 8u + -8u = 0
14 + -8u = -18 + 0
14 + -8u = -18

Add '-14' to each side of the equation.
14 + -14 + -8u = -18 + -14

Combine like terms: 14 + -14 = 0
0 + -8u = -18 + -14
-8u = -18 + -14

Combine like terms: -18 + -14 = -32
-8u = -32

Divide each side by '-8'.
u = 4

Simplifying
u = 4

See similar equations:

| 6(w+4)-4w=18 | | 2x^6+15x^3-8=0 | | X^3/x^2-9 | | 4ln((x/4)^2-1) | | -7(x-9)+7=70 | | 20x-8=40x+7 | | -3y-5y+10=36 | | 5x-15=250 | | 2-5(-1/2)= | | -0.3x+9.26=-0.7x+7.66 | | 8x-10=-10+3 | | 5(3x+9)=-41+26 | | 3(n+6)-(7n-4)=-5n | | 0.5x^2+100x-5000=0 | | 0.5x^2-100x+5000=0 | | 9(1+y)=8(y-6) | | x+17=7x+47 | | x^2+100x-10000=0 | | (x-15)(x-15)=-36 | | 15+17=-4(6x-8) | | 6(n+8)-(-4n-1)=9n | | 0=0+0 | | 15x-8=14x-12 | | 11+5x=-x+32x+39 | | (5a-2b+8ab+9)-(2a+b+8ab-1)= | | 2x-5/-2=-10 | | -3x+23y=-11 | | 2x^2-px+16=0 | | 14=-7/2x | | -16x^2+64x+4=0 | | 24=4/3w | | x^3+9x^2-7x-10=0 |

Equations solver categories